Pengaruh Variasi Rasio Pati Talas (Colocasia Esculenta L) dengan Karagenan dan Konsentrasi Pemlastis Putih Telur terhadap Karakteristik Komposit Bioplastik - Putri, Diana Hilmalia; Hartiati, Amna; Antara, I Nyoman Semadi (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 9 No 1 (2024)DO - 10.24843/JITPA/2024.v09.i01.p05, 2024)
Bioplastics are made from natural materials that can be broken down by microorganisms, so they are considered more environmentally friendly than synthetic plastics. This research aims to determine the effect of variations in the taro starch-carrageenan ratio and egg white concentration on the characteristics of bioplastic composites, determine the treatment of variations in the taro starch-carrageenan ratio and egg white concentration which produces the best treated bioplastic composites and identify the functional groups of the best treated bioplastic composites. This research used a factorial randomized block design with two factors, that was variations in the ratio of taro tuber starch-carrageenan raw materials and egg white concentration. The variables observed were tensile strength, elongation at break, elasticity, thickness expansion, biodegradation, and identification of functional groups for the best treatment. The results of the research showed that treatment with variations in the ratio of taro tuber starch to carrageenan had an effect on elasticity, elongation at break, swelling, biodegradation, tensile strength, while egg white plasticizer had an effect on tensile strength, elasticity, thickness development and biodegradation, and had no effect on elongation at break. The best characteristics of the bioplastic composite were the taro starch: carrageenan ratio of 50:50 and egg white concentration of 30% (1.5 g) with a tensile strength value of 3.21 ± 0.66 MPa; elongation at break 4.74 ± 0.78%; elasticity 119.35±17.94 MPa; thick development 53.54 ± 10.25% and biodegradation 6 days. The identified functional groups of bioplastic constituent materials show that in the best treated bioplastic composites several groups were found missing, namely ketone, alkyne and carboxylic acid groups and no new functional groups were found in the best bioplastics.